Cortical and subcortical gray matter shrinkage in alcohol-use disorders: a voxel-based meta-analysis. (July 2016) - Yang, Xun; Tian, Fangfang; Zhang, Handi; Zeng, Jianguang; Chen, Taolin; Wang, Song; Jia, Zhiyun; Gong, Qiyong
Graphical abstract: Highlights: A meta-analysis was conducted to characterize GM changes in AUD patients. Signed Differential Mapping, a novel voxel-based meta-analytic method, was used. AUD patients exist GM abnormalities in corticostriatal-limbic circuits. GM reduction in the striatum is negatively related to duration of alcohol dependence. GM shrinkage in the frontal gyrus and thalamus connect with lifetime alcohol consumption. Abstract: Although gray matter (GM) damages caused by long term and excessive alcohol consumption have long been reported, the structural neuroimaging findings on alcohol-use disorders (AUD) are inconsistent. The aim of this study was to conduct a meta-analysis, using a novel voxel-based meta-analytic method effect-size signed differential mapping (ES-SDM), to characterize GM changes in AUD patients. Twelve studies including 433 AUD patients and 498 healthy controls (HCs) were retrieved. The AUD group demonstrated significant GM reductions in the corticostriatal-limbic circuits, including bilateral insula, superior temporal gyrus, striatum, dorsal lateral prefrontal cortex (DLPFC), precentral gyrus, anterior cingulate cortex (ACC), left thalamus and right hippocampus compared to HCs. GM reduction in the right striatum is significantly negatively related to duration of alcohol dependence, while GM shrinkage of the left superior, middle frontal gyrus, and left thalamus is related to lifetime alcohol consumption. The findings demonstrate that the GM abnormalities caused by AUD are in corticostriatal-limbic circuits whose dysfunctions may involve in craving and observed functional deficits.